PERANCANGAN SISTEM INFORMASI PENJUALAN BERBASIS WEBSITE PADA DIVISI PERCETAKAN CV MEDIA ONE MART MAKASSAR - Adisha Ramdani Safitri; Andi Nur Inayatul Zahra; Amiruddin Amiruddin; Syahriah Sari (Jurusan Administrasi Niaga, Politeknik Negeri Ujung Pandang, 2023)
This research aimed to determine: 1) the design of a web-based sales information system in the Printing Division of CV Media One Mart Makassar; 2) customer perceptions of the web-based sales information system in the Printing Division of CV Media One Mart Makassar. The issue examined in this study was the digital marketing (Facebook, Instagram, Tokopedia, and Shopee) utilized in the Printing Division of CV Media One Mart Makassar, which was not managed properly. The method used in this study was the waterfall method, consisting of: 1) requirement analysis; 2) design; 3) implementation; 4) verification; 5) maintenance. Data collection techniques employed were questionnaires and interviews. The data analysis technique used was quantitative data analysis. The result of this research indicated that: 1) The design of the web-based sales information system was created using a Content Management System (CMS) through the stages of planning, visualization, designing the interface, and integrating separate elements into a cohesive whole; 2) Customer perceptions of the web-based sales information system were categorized as